The startup owner's manual. Vol. 1 : the step-by-step guide for building a great company - Blank, Steven G. (Steven Gary).; Dorf, Bob. (Pescadero, Calif. : K&S Ranch, Inc., 2012)
'The Startup Owner's Manual is what it says: a comprehensive, step-by-step guide to getting startups right. It walks entrepreneurs through the customer development process that gets them out of the building, where customers live, to develop winning products customers will buy'--back cover.
Introduction : A repeatable path ; Why a second decade? ; The four steps: a new path -- Getting started : The path to disaster : a startup is not a small version of a big company -- The path to the epiphany : the customer development model -- The customer development manifesto -- Step one : Customer discovery : An introduction to customer discovery -- Customer discovery, phase one: State your business model hypotheses -- Customer discovery, phase two :'Get out of the building' to test the problem :'Do people care?' -- Customer discovery, phase three :'Get out of the building' and test the product solution -- Customer discovery, phase four : Verify the business model and pivot or proceed -- Step two : Customer validation : Introduction to costumer validation -- Customer validation, phase one :'Get ready to sell' -- Customer validation, phase two :'Get out of the building and sell!' -- Customer validation, phase three : Develop product and company positioning -- Customer validation, phase four : The toughest question of all : pivot or proceed? -- The startup owner's manual'site' map -- Appendix A. Customer development checklists -- Appendix B. Glossary -- Appendix C. How to build a web startup : a simple overview.
Includes index.
Keywords: New business enterprises; Entrepreneurship